If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9w + -18 = 0 Reorder the terms: -18 + 9w = 0 Solving -18 + 9w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 9w = 0 + 18 Combine like terms: -18 + 18 = 0 0 + 9w = 0 + 18 9w = 0 + 18 Combine like terms: 0 + 18 = 18 9w = 18 Divide each side by '9'. w = 2 Simplifying w = 2
| ln(-3x-10)-ln(10)=3 | | -10=-6y-17 | | 2x+(90-x)+(90-x)=180 | | 36x^3-108x=0 | | -4(x+2)+4=6(x+4)+3 | | 16=-3y+1 | | (5x+1)-(-2x+7)= | | -1=-4z-19 | | -5x-7y=24 | | f(x)=5x^2-9x | | -7x^3+3x^3= | | x-.6x-.17=.33x-.27 | | -8x^2+7+9x^2-12-5x= | | 1244=0.083x+0.076(3x) | | y-(-4)=9/4(x-(-7)) | | 5x^2-11x+3-6x-13x^2= | | 16+22p=0.8986 | | 5+5p-(5p+7)-(3p+9)= | | 8x^2+3x-5-12x^2= | | 35=2x-10 | | -4xw+x-xw+6x= | | -2(2y+3)-y= | | 1.5(0.16)=0.24 | | 30t^2+t-31=0 | | -(-2v-y)+(-4y+4v)= | | 2x23/10-7 | | (16-5)x4-6/2 | | -5/7x | | -(-4v-y)-4(-5y+6v)= | | x^4+8x^3+32x^2+64x+64=0 | | 6x^7-6xy^10=0 | | s^3+12s^2-4s-48=0 |